Molecular Mechanisms of Resistance to FLT3 Inhibitors in Acute Myeloid Leukemia: Ongoing Challenges and Future Treatments - Sebastian Scholl; Maximilian Fleischmann; Ulf Schnetzke; Florian H. Heidel (Cells, 2020)
Treatment of FMS-like tyrosine kinase 3 (FLT3)-internal tandem duplication (ITD)-positive acute myeloid leukemia (AML) remains a challenge despite the development of novel FLT3-directed tyrosine kinase inhibitors (TKI); the relapse rate is still high even after allogeneic stem cell transplantation. In the era of next-generation FLT3-inhibitors, such as midostaurin and gilteritinib, we still observe primary and secondary resistance to TKI both in monotherapy and in combination with chemotherapy. Moreover, remissions are frequently short-lived even in the presence of continuous treatment with next-generation FLT3 inhibitors. In this comprehensive review, we focus on molecular mechanisms underlying the development of resistance to relevant FLT3 inhibitors and elucidate how this knowledge might help to develop new concepts for improving the response to FLT3-inhibitors and reducing the development of resistance in AML. Tailored treatment approaches that address additional molecular targets beyond FLT3 could overcome resistance and facilitate molecular responses in AML.